2012
DOI: 10.3325/cmj.2012.53.11
|View full text |Cite
|
Sign up to set email alerts
|

Double venous drainage through the superior vena cava in minimally invasive aortic valve replacement: a retrospective study

Abstract: AimTo compare the outcomes of patients who underwent upper mini-sternotomy or right mini-thoracotomy and those who underwent full sternotomy and to report a technical improvement in venous drainage by means of double venous cannulation of the superior vena cava (SVC) in mini surgical procedures.MethodsWe retrospectively analyzed the outcome of 217 patients who underwent aortic valve replacement through upper mini-sternotomy or right mini-thoracotomy at the Department of Cardiovascular Surgery, University Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…The incidence of PPM insertion was not different between the two groups although meta-analysis approached significance, finding a borderline lower incidence of PPM insertion in MS compared to RAT (OR: 0.54, 95% CI: 0.26-1.12; P = .097) ( Figure 4B). The incidence of SSI was reported in six studies, [21][22][23][24][25][26] and found to be similar between MS and RAT groups (OR: 0.65, 95% CI: 0.34-1.27; P = .209) ( Figure 4C).…”
Section: Secondary Outcomesmentioning
confidence: 75%
See 2 more Smart Citations
“…The incidence of PPM insertion was not different between the two groups although meta-analysis approached significance, finding a borderline lower incidence of PPM insertion in MS compared to RAT (OR: 0.54, 95% CI: 0.26-1.12; P = .097) ( Figure 4B). The incidence of SSI was reported in six studies, [21][22][23][24][25][26] and found to be similar between MS and RAT groups (OR: 0.65, 95% CI: 0.34-1.27; P = .209) ( Figure 4C).…”
Section: Secondary Outcomesmentioning
confidence: 75%
“…The rate of conversion to sternotomy was assessed in four studies. 18,[21][22][23] Meta-analysis found it to be significantly lower in the MS group compared to RAT (OR: 0.32, 95% CI: 0.11-0.93; P = .036) (Figure 2A). CPB was shorter for MS compared with RAT (SMD: −0.36, 95% CI: −0.13 to 0.055; P = 0.436), being reported across seven studies ( Figure 2B).…”
Section: Intraoperative Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Following opening of the pericardium and placement of pericardial stay sutures, our modified cardiopulmonary bypass (CPB) technique with direct aortic cannulation using EOPA® arterial cannula (Medtronic, Inc.) and superior vena cava (SVC) cannulation with optimized 29‐French OptiFlow venous cannula (Sorin Group) was performed (Figure 1). Surgical technique of the right minithoracotomy approach with completely central cannulation differs from the standard procedure in several steps and is previously described by Klokocovnik et al 21 with the use of double venous drainage. Ventricular vent was placed into the right superior pulmonary vein.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, our strategy may be a viable alternative when using a right lateral thoracotomy. Recently, an MIS with double venous cannulation of the superior vena cava has been described to favour complete drainage [8]. However, in our experience, the innovative small-sized, 29-Fr Optiflow cannula provides high-flow drainage across the entire cannula inserted into the right atrium without the need for double cannulation and with no increase in central venous pressure.…”
Section: Discussionmentioning
confidence: 94%